An update on90Y-ibritumomab tiuxetan in autologous stem cell transplantation (Hematology Meeting Reports, 2009)
Relapsed or refractory non-Hodgkin’s lymphoma (NHL) remains a major treatment challenge. One treatment strategy entails high-dose therapy (HDT) coupled with autologous stem cell transplantation (ASCT). In order to improve response rate, rituximab, an anti-CD20 monoclonal antibody, is widey used in combination with chemotherapy prior to or following ASCT. In addition, radiolabeled immunotherapy represents a further possible treatment refinement in this setting. Among the forms of radiolabeled immunotherapy available, 90yttrium(Y)-ibritumomab tiuxetan was the first to be approved for clinical use and has accumulated support as a treatment for relapsed or refractory NHL. One of the expanding areas of interest for 90Y-ibritumomab tiuxetan concerns its use in ASCT conditioning regimens. In this setting, 90Y-ibritumomab tiuxetan may offer improved efficacy and sparing of toxicity associated with high-dose chemotherapy and external beam total body radiation. Various dose schedules and combinations are currently under investigation and, although these have not been optimally defined, results to date show these are feasible and can provide a therapeutic advantage. The relative merits of these different approaches for treatment of NHL may be influenced by patient and disease factors.